2008
DOI: 10.1007/s00441-008-0719-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro multipotent differentiation and barrier function of a human mammary epithelium

Abstract: As demonstrated by a variety of animal studies, barrier function in the mammary epithelium is essential for a fully functioning and differentiated gland. However, there is a paucity of information on barrier function in human mammary epithelium. Here, we have established characteristics of a polarizing differentiating model of human mammary epithelial cells capable of forming a high-resistance/low-conductance barrier in a predictable manner, viz., by using MCF10A cells on permeable membranes. Inulin flux decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 64 publications
6
37
1
Order By: Relevance
“…NextBio meta-analysis revealed that expression data of 2D vs. 3D grown cells negatively correlates with data from differentiated vs. undifferentiated Caco-2 cells, 15 and with polarizing differentiating vs undifferentiated MCF10A cells. 16 This indicates that the 3D lrECM-cultured cells are more similar to the differentiated phenotype of both cell lines, consistent with previous studies showing activation of tissue-relevant phenotypic characteristics for mammary epithelial cells grown in tissue-like context. 23a Among individual transcripts in the 2D vs. 3D grown cells, SERPINB6 was the most consistently upregulated by growth in 3D lrECM (avg.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…NextBio meta-analysis revealed that expression data of 2D vs. 3D grown cells negatively correlates with data from differentiated vs. undifferentiated Caco-2 cells, 15 and with polarizing differentiating vs undifferentiated MCF10A cells. 16 This indicates that the 3D lrECM-cultured cells are more similar to the differentiated phenotype of both cell lines, consistent with previous studies showing activation of tissue-relevant phenotypic characteristics for mammary epithelial cells grown in tissue-like context. 23a Among individual transcripts in the 2D vs. 3D grown cells, SERPINB6 was the most consistently upregulated by growth in 3D lrECM (avg.…”
Section: Discussionsupporting
confidence: 90%
“…2A) 15 and from polarizing differentiating MCF10A cells in a Transwell model (P = 4.5e-45; Supplemental Fig. 2B), 16 consistent with the notion that even cells from long-term established lung cancer cell lines adopt a more differentiated phenotype when grown in 3D lrECM.…”
Section: Resultssupporting
confidence: 81%
“…Through clonogenic assays we have previously shown the presence of mulipotent cells in MCF10A cultures [35]. Here, using BrdU pulse-chase and label retention assays we have been able to visualize the position of these cells, and demonstrate their ability to give rise to the other epithelial cell layers.…”
Section: Discussionmentioning
confidence: 81%
“…For example, primary HMEC allowed to form acini in Matrigel have fivefold higher levels of hCLCA2 than cells cultured in monolayer (Dontu et al, Table S7 (Dontu, Abdallah et al 2003)). Similarly, MCF10A cultured on permeable membranes that support normal apico-basal polarization and other aspects of differentiation have an eightfold higher level of hCLCA2 than monolayers (Marshall, Pai et al 2009). A gene co-expression analysis using the Oncomine Clusters software revealed that hCLCA2 expression co-varies with epithelial markers such as claudins 1 and 8, E-cadherin, tetraspannins 1 and 7, and gap junctional proteins.…”
Section: Resultsmentioning
confidence: 99%